Rapid directed molecular evolution of fluorescent proteins in mammalian cells. (30th December 2021) - Babakhanova, Siranush; Jung, Erica E.; Namikawa, Kazuhiko; Zhang, Hanbin; Wang, Yangdong; Subach, Oksana M.; Korzhenevskiy, Dmitry A.; Rakitina, Tatiana V.; Xiao, Xian; Wang, Wenjing; Shi, Jing; Drobizhev, Mikhail; et al.
Abstract: In vivo imaging of model organisms is heavily reliant on fluorescent proteins with high intracellular brightness. Here we describe a practical method for rapid optimization of fluorescent proteins via directed molecular evolution in cultured mammalian cells. Using this method, we were able to perform screening of large gene libraries containing up to 2 × 10 7 independent random genes of fluorescent proteins expressed in HEK cells, completing one iteration of directed evolution in a course of 8 days. We employed this approach to develop a set of green and near‐infrared fluorescent proteins with enhanced intracellular brightness. The developed near‐infrared fluorescent proteins demonstrated high performance for fluorescent labeling of neurons in culture and in vivo in model organisms such as Caenorhabditis elegans, Drosophila, zebrafish, and mice. Spectral properties of the optimized near‐infrared fluorescent proteins enabled crosstalk‐free multicolor imaging in combination with common green and red fluorescent proteins, as well as dual‐color near‐infrared fluorescence imaging. The described method has a great potential to be adopted by protein engineers due to its simplicity and practicality. We also believe that the new enhanced fluorescent proteins will find wide application for in vivo multicolor imaging of small model organisms.